NECROTIZING FASCIITIS: a surgical challenge in contemporary clinical practice - Okhunov, A.O.; Erkulov, A.Sh. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Necrotizing fasciitis (NF) is a rapidly progressing, life-threatening soft tissue infection that demands immediate surgical intervention. Despite being a rare condition, it is associated with high morbidity and mortality rates due to its fulminant course and systemic complications. This review article summarizes current surgical strategies in the treatment of necrotizing fasciitis based on recent literature. Emphasis is placed on the timing and extent of debridement, the role of repeated surgical revisions, amputation criteria, and the integration of adjunctive therapies such as negative pressure wound therapy and reconstructive procedures. We also analyze clinical decision-making in patients with comorbidities including diabetes mellitus and immunosuppression. The article highlights the importance of early recognition, radical surgical tactics, and a multidisciplinary approach in improving patient outcomes. By reviewing global surgical experiences and evidence-based recommendations, we aim to provide a comprehensive perspective on the optimal management of necrotizing fasciitis.